Pengaruh pertumbuhan penduduk, inflasi, investasi, upah minimum dan kesempatan kerja terhadap pengangguran di Kota Jambi - Chandra, Aditya Surya; Yulmardi , Yulmardi; Erfit, Erfit (Jurnal Paradigma Ekonomika, 2020)
This study aims to: 1) To analyze the development of population growth, inflation, investment, minimum wages, job opportunities and unemployment in Jambi City during 2001-2017., 2) To determine and analyze the effects of population growth, inflation, investment, minimum wages and job opportunities for unemployment in Jambi City during 2001-2017. Based on the research results, it can be concluded that the structural equation I show that the development of population growth, inflation, investment, minimum wages, and job opportunities has fluctuated every year, as well as the unemployment variable which fluctuates annually. Based on the results of the t-test on multiple linear regression, it can be concluded that only the job opportunity variable affects unemployment because the probability is less than 0.05.